THE ROLE OF SYSTEMIC INFLAMMATION IN DECREASE OF ELASTICITY OF MAGISTRAL ARTERIES AND IN PROGRESSION OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH SYSTEMIC HYPERTENSION, ObESITY AND TYPE 2 DIAbETES - M. E. Statsenko; M. V. Derevyanchenko (Российский кардиологический журнал, 2018)
Aim. To evaluate the role of systemic inflammation in decrease of magistral arteries elasticity and progression of endothelial dysfunction in arterial hypertension (AH) patients comorbid with obesity and/or type 2 diabetes (DM2).Material and methods. Ninety patients with AH stages II-III, 45-65 year old, were selected to 3 groups. Group 1 — patients with “isolated” AH, group 2 — AH with obesity, group 3 — AH and DM2 patients. Standard physical examination was done, vascular stiffness assessment by pulse wave velocity (PWV) measurement of the vessels of muscular (PWVm) and elastic (PWVe) types; the levels were measured of systemic inflammation markers, endothelial dysfunction and fibrosis.Results. PWVe and PWVe >10 m/s were significantly more common in group 3 patients comparing to group 1 (10,3 [9,5;11,7] vs 9,0 [8,0;11,3] m/s and 70 vs 40%, respectively). Concentration of C-reactive protein (CRP) was significantly higher in AH with DM2 comparing to AH and obesity or only AH (7,92 [4,77;16,15] vs 4,77 [4,53;5,43], 7,92 [4,77;16,15] vs 2,98 [0,65;7,19] mg/L, respectively). Level of endothelin-1 (E1) in blood serum increased significantly in 1 to 3 group, with significant differences in all groups. In AH and DM2 patients, concentration of collagen type 4 in the blood was statistically significantly higher than in AH and obesity patients and only AH (5,67 [3,58;9,20] vs 2,94 [2,57;8,45], 5,67 [3,58;9,20] vs 2,63 [2,23;7,28] ng/mL). Correlational analysis showed the presence of highly significant correlations in concentrations of CRP and PWVe (r=0,41), level of E1 (0,51), in E1 and duration of DM2 anamnesis (r=0,58), body mass index (r=0,35), smoking (r=0,54), PWVm (r=0,47), PWVe (r=0,47), in concentration of collagen type 4 and duration of DM2 anamnesis (r=0,36), PWVe (r=0,31). Conclusion.  The data obtained witness on the negative influence of systemic inflammation on the elasticity of vascular wall of magistral arteries, and on its importance in progression of endothelial dysfunction in AH patients comorbid with obesity and DM2.